2021
DOI: 10.3389/fneur.2021.687740
|View full text |Cite
|
Sign up to set email alerts
|

As Time Goes by: Understanding Child and Family Factors Shaping Behavioral Outcomes After Traumatic Brain Injury

Abstract: Objective: To model pre-injury child and family factors associated with the trajectory of internalizing and externalizing behavior problems across the first 3 years in children with pediatric traumatic brain injury (TBI) relative to children with orthopedic injuries (OI). Parent-reported emotional symptoms and conduct problems were expected to have unique and shared predictors. We hypothesized that TBI, female sex, greater pre-injury executive dysfunction, adjustment problems, lower income, and family dysfunct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 78 publications
1
6
0
Order By: Relevance
“…There was a tendency for improvement between the first and second year, but this was only temporary, with a nonsignificant increase between the second and the seventh year in the proportion of participants above the clinical cutoff for internalizing and externalizing problems. These results support the continuity of behavioral problems over time and are in line with previous studies suggesting that behavioral problems emerge soon after injury and, once present, these difficulties tend to become persistent (Ewing-Cobbs et al, 2021;Schwartz, 2003).…”
Section: Persistence Of Behavioral Problems Over Timesupporting
confidence: 91%
“…There was a tendency for improvement between the first and second year, but this was only temporary, with a nonsignificant increase between the second and the seventh year in the proportion of participants above the clinical cutoff for internalizing and externalizing problems. These results support the continuity of behavioral problems over time and are in line with previous studies suggesting that behavioral problems emerge soon after injury and, once present, these difficulties tend to become persistent (Ewing-Cobbs et al, 2021;Schwartz, 2003).…”
Section: Persistence Of Behavioral Problems Over Timesupporting
confidence: 91%
“…The need to exclude the parental employment variable contrasts with findings in the literature indicating that SES has an impact on a child’s ability to recover from injury and post-injury therapy [ 62 ]. Lower family income has been associated with a higher percentage of pediatric TBI mortality [ 63 ] and higher levels of emotional difficulties and conduct problems at 12 months post-injury [ 64 ]. The lack of employment variability may explain why this variable was not included in the SEM model; the majority of households had at least one parent employed for more than 35 h a week (87.3% of households in our sample), compared to households where parents worked less (10.3%).…”
Section: Discussionmentioning
confidence: 99%
“…In line with our results, Jones et al (2021) report difficulties in executive, emotional, and behavioral domains 7 years following an mTBI. Another study reports psycho-emotional problems that persist up to 2 years following a TBI (Ewing-Cobbs et al, 2021). However, still other studies report behavioral difficulties that had either subsided 1 year after mTBI (Maillard-Wermelinger et al, 2009) or parent-rated executive functioning that showed an improving trajectory 2 years following TBI .…”
Section: Executive Function Impulsivity and Emotion-regulationmentioning
confidence: 99%
“…Further, persistent emotional problems have frequently been reported following mTBI in children (Emery et al, 2016;Ewing-Cobbs et al, 2021;Gagner, Landry-Roy, Bernier, Gravel, & Beauchamp, 2018;Jones et al, 2021). In addition to simply experiencing negative emotions, emotional problems may be due to impairments in cognitive control and subsequent difficulties in the regulation of such emotions.…”
Section: Introductionmentioning
confidence: 99%